Elimination of basis set superposition error in linear-scaling density-functional calculations with local orbitals optimised in situ - Haynes,PD; Skylaris,CK; Mostofi,AA; Payne,MC (CHEM PHYS LETT, 2006)
Basis set superposition error (BSSE) in density-functional calculations occurs when the extended Kohn-Sham orbitals are expanded in localised basis sets. but is absent when a plane-wave basis is used. Elimination of BSSE is essential for the accurate description of intermolecular forces. Linear-scaling methods are formulated in terms of local orbitals, making plane-waves an inappropriate choice of basis. In this work the BSSE in linear-scaling methods is studied in the context of hydrogen bonds. In particular it is shown that BSSE is eliminated by optimizing the local orbitals in situ using a systematic basis set equivalent to a set of plane-waves. (c) 2006 Elsevier B.V. All rights reserved.